Effectiveness of student involvement theory through co-curricular development in college context : enhancement of societal transformation - Sebake, B. K. (International Conference on Public Administration and Development Alternatives (IPADA), 2018)
Higher Education Institutions in South Africa and elsewhere in the world aspire to produce well rounded graduates that feed into active sectors of the society and add value. Apart from the above, students at universities and colleges are supposed to be at the cutting edge of innovation through balancing their academic life, and outdoor learning activities in order to balance amongst others, their psychological, intellectual and social beings. In light of the above, student involvement theory provides an opportunity to inculcate and assert both the theoretical grounds and empirical nature through utilisation of co-curricular development to contribute in a journey of societal transformation, with important pillars being: cultural awareness, social development and justice, and diversity. The fundamental enquiry of the paper is whether in the journey of this transformation, is student involvement theory effective and co-curricular activities have impact on the contribution towards societal transformation and how? The attention will be drawn from conceptual framework of student involvement theory, framework models of co-curricular, effectiveness of outdoor learning activities towards personal development, quality student engagements, and quality promotion in co-curricular activities. The above assist in affirming the importance of co-curricular activities in complementing the quality student experience, which in turn student involvement theory will be proven effective within universities and college context. The paper is conceptual in nature through analysis of the desk top literature and testing the empirical evidence in order to assess the effectiveness, with conclusion to be made without any recommendation.
Journal article published in the 3rd Annual International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Co-curricular development; Cultural awareness; Diversity Student involvement theory; Transformation; Student activities; Universities and colleges -- Curricula; Social change